Two Rb-Sr Whole Rock Isochrons from Plutons In the Cobequid Highlands, Nova Scotia, Canada - Donohoe, H.; Keppie, J.; Halliday, A. (Atlantic Geology, 1986)
Two Rb-Sr Hhole rock Isochrons have been obtained froi plutons In the Cobequld Highlands of Nova Scotia: the Debert River and Hart Lake-Byers Lake Plutons. The undeforied, info I lated Debert River Pluton yielded an age of 596± 70 Ma and an Initial ^Sr/^Sr ratio of 0.7059 ± 0.0007. This age places an upper age I lilt on the detonation recorded In the Fol ly River Schist (youngest unit of the Bass River Coaplex), the d I or I tic Frog Lake Pluton, and the sedlaerttary rocks iMedlately north and east of the Debert River Pluton. The Hart Lake-Byers Lake Pluton yielded anageof348±5Maandan Initial ^Sr/^Sr ratio of 0.7046 ± 0.0008. The slii I larlty of this age to that of the adjacent felslc vol can I cs of the Byers Brook For nation suggests that they are ccaagntlc and confine that a Carboniferous igjieous event fons an Inportant part of the geological history of the Cobequld Highlands. The Initial ^Sr/^r ratio and the blotite-hornblende content of the two granites suggest a eaflc Igneous loner crustal source or possible untie component for the eapa.